THE APPEARANCE OF PHENOTYPIC CHARACTER ON FIVE GENOTYPES OF CAYENNE PEPPER - Eva Oktaviani; Neni Rostini; Agung Karuniawan (Jurnal Penelitian Saintek, 2018)
This study was aimed at determining the appearance of phenotypic characters in five cayenne genotypes in Sukamantri, Ciamis Regency. The research method used was the experimental method with Randomized Block Design (RBD) with five treatments repeated five times. Data were analyzed by variance and followed by Least Significant Difference (LSD) Test. The testing material consisted of five genotypes of cayenne pepper, namely one of the new superior varieties (Ratuni Unpad), and four varieties (CR8873, Dewata, Taruna, and Rabani). The tests were carried out in Sukamantri, Ciamis Regency in 983 m asl in August 2017 to February 2018. The observations were made on the character of the results and components of results which included the seed length, the seed diameter, the seed weight per unit, the seed weight per plant, the seed weight per plot, and the seed weight per hectare. The test results showed that there were differences in phenotypic characters between the five genotypes tested. The Dewata, Ratuni Unpad, and CR8873 genotypes show the highest potential yield (8.34 tons/ha, 7.71 tons/ha, and 7.24), with the character of fruit weights per fruit of 1.382 grams, 0.911 grams respectively. and 1,311 grams.PENAMPILAN KARAKTER FENOTIPIK HASIL PADA LIMA GENOTIP CABAI RAWITPenelitian ini bertujuan untuk mengetahui penampilan karakter fenotipik pada lima genotip cabai rawit di Sukamantri, Kabupaten Ciamis. Metode penelitian yang digunakan adalah metode eksperimen dengan Rancangan  Acak  Kelompok  (RAK)  dengan  lima  perlakuan  diulang  lima  kali. Data dianalisis dengan sidik ragam dan dilanjutkan dengan Uji Least Significant Difference (LSD). Bahan pengujian terdiri atas lima genotip cabai rawit, yaitu salah satu varietas unggul baru (Ratuni Unpad), dan empat varietas (CR8873, Dewata, Taruna, dan Rabani). Pengujian dilakukan di Sukamantri, Kabupaten Ciamis dengan ketinggian tempat 983 m di atas permukaan laut (dpl.) pada Agustus 2017 sampai Februari 2018. Pengamatan dilakukan terhadap karakter hasil dan komponen hasil yang meliputi panjang buah, diameter buah, bobot buah per buah, bobot buah per tanaman, bobot buah per plot, dan bobot buah per hektar.Hasil pengujian menunjukkan bahwa terdapat perbedaan karakter fenotipik antarlima genotip yang diuji. Genotip Dewata, Ratuni Unpad, dan CR8873 menampilkan potensi hasil yang tertinggi (8,34 ton/ha; 7,71 ton/ha; dan 7,24); dengan karakter bobot buah per buah masing-masing sebesar 1,382 gram; 0,911 gram; dan 1,311 gram.